An Eye-Tracking Study of Sketch Processing: Evidence From Russian - Petrova, Tatiana E.; Riekhakaynen, Elena I.; Bratash, Valentina S. (Frontiers in Psychology, 2020)
This study investigates the online process of reading and analyzing of sketchnotes (visual notes containing a handwritten text and drawings) on Russian language material. Using the eye-tracking method, we compared the processing of different types of sketchnotes (‘path’ (trajectory), linear, and radial) and the processing of a verbal text. Biographies of Russian writers were used as the material. In a preliminary experiment, we asked 89 college students to read the biographies and to evaluate each text or sketch using five scales (from -2 to +2). The best example for each of three formats of sketchnotes and a verbal text were chosen. In the main experiment, twenty-one secondary school students examined four different biographies in four different formats (three sketchnotes and a verbal text), answered to the factual and analytical questions to these texts and estimated the difficulty of each text. We measured the total dwell time, the total fixation count, the average fixation duration for each stimulus as well as for separate zones inside the sketches including verbal and non-verbal information. Our results show that readers process the information better and faster while reading sketchnotes than a verbal text. In the trajectory sketchnotes, the readers followed the order of elements aimed by the author of the sketchnotes better than in the radial and linear sketchnotes. The analysis of participants’ eye movements while processing the stimuli made it possible to propose several recommendations for creating effective sketchnotes.